Lattice structures with stiffness gradient for loads transfer at bone-prosthesis interface (Transactions on Additive Manufacturing Meets Medicine, 2019)
The fabrication of prostheses for orthopedic implants exploits additive technologies based on powder micromelting. The shape modularity, the biocompatibility of materials and the qualification procedures required by normative motivated the application of additive manufacturing since several years. The bone-prosthesis interface has great importance in implant integration, preventing prosthesis rejection and limiting time-scheduled prosthesis replacements. The load transfer between metal structures and bone requires precise modulation to stimulate the strength of new tissues. The design of lattice structures based on modular 3D stiffness variation is described in this paper, with special focus on the modeling methods based on homogenization approach.